Lecturers’ working time and their achievement of key performance indicators within a code of ethics - Kamaruddin, Zumahiran; Ahmad Sarkawi, Azila (Pusat Tamhidi, Universiti Sains Islam Malaysia, 2016)
Academics of higher learning institution in Malaysia have their performance measured by Key Performance Indicators (KPIs). At International Islamic University Malaysia (IIUM), KPIs for academics comprises six key areas namely teaching, research, publication, supervision, consultancy and services to public. These areas are measured from various operational and functional aspects of the academics whose official working time per week is forty hours. This study aims to investigate the potential of achieving these KPIs within the allocated working time incumbent upon the University Code of Ethics. The objectives are: 1) to examine the viability of those KPIs in relation to lecturers’ working time and the University Code of Ethics, and 2) to suggest strategies/policies towards holistic achievement of KPIs. Consequently, the Department of Applied Arts and Design was selected to represent the Kulliyyah of Architecture and Environmental Design, IIUM. The class schedule of 2014-2015-2016 academic session was analysed to tabulate lecturers’ teaching time and number of students that they teach. Teaching constitutes the main bulk of their work load, followed by supervision, research and administration. Then, semi-structured interviews with the seven full-time academics were conducted to verify the staff workload and working time. The study found that 24 (60%) out of 40 hours per week during the two normal semesters were spent for teaching and its related matters like marking of assignments and students’ consultation. Enormous hours were dedicated for teaching and tutorial session, supervision of undergraduate research project and postgraduate students, while lecturers still have to allocate some times for administration works. Shortage of time is a real issue for the lecturers to fully achieve their KPIs whilst avoiding deviations from the University code of ethics. Thus, more holistic and realistic KPI and strategies are needed besides effective human resources for quality academic services and integrity.